Downregulation of CacyBP by CRISPR/dCas9-KRAB Prevents Bladder Cancer Progression - Zheng, Hanxiong; Chen, Chiheng (Frontiers in Molecular Biosciences, 2021)
Bladder cancer (BCa) is a leading cause of cancer-related death in the world. CacyBP is initially described as a binding partner of calcyclin and has been shown to be involved in a wide range of cellular processes, including cell differentiation, proliferation, protein ubiquitination, cytoskeletal dynamics and tumorigenesis. In the present study, we found that CacyBP expression was significantly upregulated in BCa tissues compared with adjacent normal tissues. Moreover, its expression was negatively correlated with overall survival time. Secondly, CacyBP had higher expressions in BCa cell lines than normal urothelial cells which was consistent with the results of BCa tissues. Finally, knockdown of CacyBP by CRIPSR-dCas9-KRAB in T24 and 5637 BCa cells inhibited cell proliferation and migration by CCK-8 assay and scratch assay, and promoted apoptosis by caspase-3/ELISA. These data elucidate that CacyBP is an important oncogene contributing to malignant behavior of BCa and provide a potentially molecular target for treatment of BCa．